CGRP-targeted therapy fulfilling the treatment gap in medication-underuse setting: a retrospective cohort study at a tertiary headache center in Thailand, a lower-middle-income country - Sirawit Roongrojwittayakul; Prakit Anukoolwittaya; Akarin Hiransuthikul; Thanakit Pongpitakmetha; Sekh Thanprasertsuk; Wanakorn Rattanawong (The Journal of Headache and Pain, 2025)
BACKGROUND: Migraine preventive treatment is essential to reducing the burden of disease. However, discontinuation of oral migraine preventive medications (OMPMs) remains common due to suboptimal efficacy and tolerability, especially in lower-middle-income countries, which may contribute to migraine progression-a situation that has led to the introduction of the concept of "Medication Underuse Headache". The calcitonin gene-related peptide monoclonal antibody (CGRP mAbs) might close the gap in this situation. This study aimed to investigate the treatment patterns of migraine preventive medications over six months at a tertiary headache center in Thailand and to explore the association between each preventive medication class and discontinuation rates. METHODS: A single-center retrospective cohort study was conducted between 2021 and 2023. Adult patients who were diagnosed with migraine and received at least one preventive medication at their first visit to the Headache Clinic at King Chulalongkorn Memorial Hospital were included, with a minimum follow-up period of six months. The primary outcome was the discontinuation of any migraine preventive medication from the baseline regimen during follow-up visits. A multivariable Cox regression model, adjusted for sex, age, and diagnosis, was used to explore baseline factors associated with the discontinuation of preventive migraine medications. RESULTS: Among the 100 eligible patients (mean age [SD]: 39.6 [14.4] years; 87.0% female), 41.0% (41/100) discontinued at least one preventive medication, most commonly due to intolerance to side effects (53.7%, 22/41) and lack of treatment effectiveness (34.1%, 14/41). The highest discontinuation rates were observed with serotonin norepinephrine reuptake inhibitors at 53.8% (7/13), calcium channel blockers at 37.5% (6/16), and beta-blockers at 25.6% (11/43). Notably, no patients discontinued CGRP mAbs. Patients using CGRP mAbs at baseline had a significantly higher rate of discontinuing at least one other oral preventive medication compared to those who did not use CGRP mAbs: 31.7% vs. 25.4% at month 3, and 55.4% vs. 33.4% at month 6 (p = 0.04). After adjustment, baseline use of CGRP mAbs was significantly associated with an increased risk of discontinuing at least one medication in the regimen (adjusted odds ratio 2.16; 95% CI: 1.16 to 4.03, p = 0.02). CONCLUSION: Discontinuation of preventive migraine treatment remains a significant issue in Thailand. CGRP mAbs were associated with higher treatment persistence and may help reduce polypharmacy in migraine management.
Keywords: Migraine and Headache Studies; Medication Adherence and Compliance; Respiratory and Cough-Related Research